Fabrication of superhydrophobic and oleophobic zinc coating on steel surface. Issue 11 (24th July 2017) - Yu, Sirong; Li, Hao
ABSTRACT: In this work, a simple method, including electrodeposition and chemical modification, for fabrication of a superhydrophobic and oleophobic coating on steel substrate is reported. The surface morphology of this coating showed concave structure, and the contact angles of water and glycerol on this coating surface were about 153.57° and 149.32°, respectively. In addition, the water droplet was easy to roll on this coating surface, and the sliding angle was smaller than 10°. The contact angle of the water/ethanol droplet with different surface tension, from 56 to 36 mN m −1, was also >130° on this coating surface, indicating this as superhydrophobic and oleophobic coating surface with good lyophobicity. Moreover, this coating surface had excellent non-sticking property for the water droplet under a certain external pressure, self-cleaning property and long-term stability.